Abundance Study of Koompassia excelsa in Maintaining Conservation of Ecosystems in Tangkahan Langkat Nature Reserve, North Sumatra - Pandu Prabowo Warsodirejo; Asri Safitri Hasibuan; Arifin Ritonga; Lia Listiana (Bioscience, 2020)
Writing this paper aims to introduce the king's wooden tree (Koompassia excelsa) to the general public, as the background of this writing because North Sumatra especially in the Tangkahan Langkat forest has one tree with a height of almost 88 meters with very large roots and very hard wood, but not much people know it, this can happen because of lack of exposure and lack of publicity both directly and with the mass media. The method used in this study is the Exploration Method and directly record the sample during the trip. The area observed in the data collection process is 40 hectares divided into 2 regions, namely Region A (15 Hectares) and Region B (25 Hectares). The purpose of this study is to explain that the Koompasia excelsa species is an original species called Timber The king and saw its abundance in the Gunung Leuser Tangkahan Langkat Forest which is adjacent to the Natural Protection Forest of Bukit Barisan National Park in North Sumatra. Based on the results of research in the Gunung Leuser National Park Forest area, North Sumatra it can be concluded that the tualang tree can be found in lowland habitats with altitudes reaching 350 m above sea level and slope rates varying from 40-60. The dominance of species and associations is one of the factors that influence the adventure habitat, but that does not mean that other species do not influence the adventure habitat, such as altitude, soil type, and species of animals that have not been observed and analyzed further. In addition, it is necessary o carry out an inventory of adventurers to estimate the population in North Sumtatra, so that if there is a decline in population, conservation status can be improved.